An Experimental Study to Investigate the Potential of Online Shopping in Immersive Virtual Realities Compared to Conventional Online Shops - Engelmann, Tanja; Wallstein, Sabine; Hitzler, Dieter (International Journal of Virtual Reality, 2019)
Immersive virtual reality technology enables the experience of feeling ‘presence’, that is, to have the feeling of being in an immersive computer-supported room. Because these technologies are used increasingly in private households, retailers are very interested in using them as a new sales opportunity. In our experimental study we investigated whether VR-based online shops could be more profitable for them compared to conventional online shops. The following results were found: A VR-based online shop generated a more real perception of the objects, and more interest in buying them. In addition, the shopping experience in the VR-based online shop was perceived as very exciting. However, the amount of acquired knowledge and the influence on the attitude of the buyer seemed to depend on the object type. Despite the limitations of this experimental study due to its focus on internal validity, the results point to the potential of immersive VR-based online shops as a new distribution channel.